"Modern pedagogical rhetoric" in the preparation system of Doctors of Philosophy - Krasnytska, Olha (Technium Social Sciences Journal, 2020)
The aim of the article is to cover the content of the author’s course "Modern pedagogical rhetoric" in the preparation system of doctors of philosophy - future teachers of higher military education establishments. The preparation system of doctors of philosophy at the third (educational-scientific) higher education level is analysed in the article. The role of rhetoric as a science of public speaking and eloquence in the process of preparation of future teachers, scientists of higher military educational establishments was shown. The content of the author’s course "Modern Pedagogical Rhetoric", which has been tested for three years, was revealed. The purpose of the discipline is to develop the rhetorical competence and rhetorical culture of a future teacher of a higher military school, a scientist, and to form his positive image. The program of the course "Modern Pedagogical Rhetoric" contains four main topics: the basics of public speaking of a teacher of a higher military school, the rhetorical culture of a teacher of a higher military school, the proficiency in preparing and conducting public speaking, the art of argumentation and polemics in the activities of a teacher of a higher military school. The first topic covers the concepts of rhetoric, public speaking and eloquence, pedagogical rhetoric, the principles of oratorical art, types and kinds of public speeches, ways of audience management during public speaking, peculiarities of listener’s perception of information, a pedagogical image of the teacher. The second topic focuses on the development of rhetorical culture, in particular, the technique and culture of speech. The third topic reveals the peculiarities of public speaking preparation, the subtleties of interaction with the audience, the construction of public speeches, their structure, the differences between informative and persuasive speeches. The fourth topic is aimed at mastering the art of argumentation and controversy, defines the features of logical and emotional argumentation in public speaking, rules of discussion, disputes, controversy, techniques for answering questions from the audience.